2005
DOI: 10.1002/ddr.20026
|View full text |Cite
|
Sign up to set email alerts
|

Galanin receptors as novel drug targets for the treatment of depression and anxiety

Abstract: The neuropeptide galanin and its three receptors are widely distributed throughout the mammalian brain, with highest levels in limbic brain nuclei. Galanin is co-localized with classical neurotransmitters, including acetylcholine and the monoamines serotonin and noradrenaline. Behaviorally, the galaninergic system regulates numerous cognitive and affective behaviors that are essential for normal homeostasis. Recently, a large body of preclinical evidence suggests that galanin and its receptors represent putati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In contrast, there is no evidence so far for GAL1-R expression in human skin (Bovell et al, 2012;Dallos et al, 2006). It is well known that GAL receptors are expressed in rodent skin as well; however, the lack of specific GAL receptor antibodies for this species explains the deficit of data regarding the cellular distribution of GAL receptors on mouse and rat skin (Lu et al, 2005). As a vasoactive peptide, GAL is able to block plasma extravasation induced by different stimuli such as histamine, substance P, or antidromic C fiber stimulation in rodent and pigeon skin (Jancso et al, 2000;Xu et al, 1991).…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, there is no evidence so far for GAL1-R expression in human skin (Bovell et al, 2012;Dallos et al, 2006). It is well known that GAL receptors are expressed in rodent skin as well; however, the lack of specific GAL receptor antibodies for this species explains the deficit of data regarding the cellular distribution of GAL receptors on mouse and rat skin (Lu et al, 2005). As a vasoactive peptide, GAL is able to block plasma extravasation induced by different stimuli such as histamine, substance P, or antidromic C fiber stimulation in rodent and pigeon skin (Jancso et al, 2000;Xu et al, 1991).…”
Section: Introductionmentioning
confidence: 98%
“…Searches were also conducted using specific behavioural models/tests or mushroom species as keywords. Studies were limited to those using rodent species as those reflect the expertise of the authors ( Lu et al, 2005 ; Barr et al, 2006 ; Hill et al, 2007 ; Boyda et al, 2014 ); however, it is important to note that other species, such as zebrafish, represent additional valid animal models of antidepressant efficacy ( Braun et al, 2024 ).…”
Section: Methodsmentioning
confidence: 99%
“…Morphological studies revealed a wide distribution of galanin-like immunoreactivity in both peripheral and central nervous systems, and galanin has since been shown to regulate numerous biological processes: neurotransmitter and hormone release [4,5], feeding [6] and endocrine function [7,8], pain threshold [9][10][11], seizure activity [12], LTP [13,14], learning and memory [10,15], neurogenesis and neuro-protection [16][17][18][19][20]. Recently, the role of galanin in mood disorders has attracted a great deal of interest [15,[21][22][23] as there has always been an urgent need for the development of novel antidepressants with faster onset, higher efficacy, fewer side effects, and for treatment resistant cases (with SSRIs, TCAs and MAO- inhibitors) that occur in about 30% of depression patients. A close link between the galanin and momoamine systems has been established and galanin injection into the hypothalamus has been shown to affect feeding and to regulate stress response.…”
Section: Introductionmentioning
confidence: 99%